Thyroid Diseases Are an Underestimated Risk Factor for Cerebral Venous Sinus Thrombosis - Hieber, Maren; von Kageneck, Charlotte; Weiller, Cornelius; Lambeck, Johann (Frontiers in Neurology, 2020)
Introduction: Cerebral venous sinus thrombosis (CVST) is a rare disease that generally accounts for just 1% of all strokes. Of the multiple risk factors that have been identified, the most common are genetic or acquired thrombophilia and the use of oral contraceptives, while the less common include local infections and mechanical causes. Thyroid diseases have been described as rare risk factors for CVST (<2% of all cases), without exact knowledge of the underlying pathophysiology. This retrospective study aimed to re-evaluate the relevance of thyroid disease as risk factor for CVST, with particular emphasis on hyperthyroidism. Patients and Methods: Confirmed cases of CVST were (re-)evaluated in terms of risk factors including thyroid parameters. Results were compared to previous data from the International Study on CVST. Results: Between 1996 and 2016, 182 patients with confirmed CVST were treated in our hospital with a median age of 44 years and a female proportion of 74.7%. Genetic or acquired thrombophilia along with the use of oral contraceptives were found to be the most common risk factors. Thyroid diseases were present in 20.9% of CVST patients; this included patients with previous (9.9%) and current thyroid dysfunction (11%). Discussion and Conclusions: Thyroid diseases may represent a more common risk factor for CVST than previously described. This holds true even if patients with current thyroid dysfunction are purely taken into account. However, 58% of patients had more than one additional risk factor, suggesting a multifactorial hypercoagulability. Clinical Trials Register: Registered at the German Clinical Trials Register: http://www.drks.de, DRKS00017044.